Impact of Indonesia's Non-Toll Road Policy on Travel Cost-Time - Dhanang Tiar Rendra; Muhammad Halley Yudhistira (Universitas Negeri Semarang, 2025)
This study aims to provide empirical evidence on whether non-toll road construction, as a government investment (National Strategic Project) in the transport infrastructure sector, impacts local economic activity at the village level. It fills a gap in the literature by adopting a Difference-in-Differences (DiD) approach and analyzing at the village level using PODES data, comparing villages affected by the policy (treatment group) with those that were not (control group). Key outcome variables derived from PODES data include travel time and cost to sub-district and district centers. To ensure robustness, the analysis includes fixed effects for time and location, and placebo tests are conducted to validate the assumption of parallel trends. The results show that non-toll road construction leads to a statistically significant reduction in travel time by 21% and travel costs by 30.9%, associated with improved access to government services and modest growth in local economic indicators such as market activity, employment, or business formation.